Assessing Rutting Potential of Stone Mastic Asphalt Using Wheel Tracker and Dynamic Modulus Testing - Imran Hafeez; Mumtaz Ahmad Kamal; Muhammad Waseem Mirza (The Baltic Journal of Road and Bridge Engineering)
Rutting potential of stone mastic asphalt with varying aggregate gradations was assessed in the past mainly by uniaxial compression testing which is not the only test to predict its true performance in the field. Dynamic testing and accelerated wheel tracking test are considered the most suitable laboratory test procedures. Four stone mastic asphalt mixtures were prepared in this study using PG 58-22 binder, Viatop plus CT-40 fiber and four aggregate gradations with nominal maximum sizes of 9.5 mm, 12 mm, 19 mm and 25.4 mm. To access the effects of aggregate gradations, single type of bitumen, filler and fiber was used. Mixtures were tested and evaluated under both type of testing procedures at different temperature levels. A regression model was developed using wheel tracker test data to ascertain significant parameters that are directly influencing the rut depth. The statistics of the model shows an excellent degree of determinacy of 0.92 and a relative accuracy of 0.29. Sigmoidal functions using Witczak equations were determined from dynamic modulus master curves for characterization of mixes and compared with previous studies. Correlation between the wheel tracking factor and a dynamic modulus factor was also established at three frequency levels. The study reveals that a reasonable relationship exists between the wheel tracking factor and dynamic modulus factor for stone mastic asphalt mixtures.